NIVEL DE SATISFACCIÓN DE LOS CLIENTES EN EL ALMACÉN CREDIFACIL DEL CANTÓN MONTALVO - Camacho Vargas, Jimmy Javier (2018)
Customer satisfaction is considered one of the main factors to be taken into account in the sales market in all companies in the world, this is because it represents a central point when making decisions, especially in a changing environment ; since it indicates the level of encouragement of an individual as a result of the comparison between the perceived performance of the product or service purchased with the expectations established before making the purchase. Companies currently continuously conduct customer perception surveys to determine their levels of satisfaction with the products they buy, this allows them to make decisions about which strategies can be used to increase satisfaction or to correct any problems presented to customers. , as an internal feedback process; This allows companies to better manage their resources for the benefit of customers.